REPRESENTASI NERAKA DALAM ANIME "HOOZUKI NO REITETSU” - Andiza Azza Suhadi (Japanology: The Journal of Japanese Studies, 2019)
In Japanese people belief hell is place in the afterlife where sinners and ungodly people get tortured. But it also often appears in Japanese pop-media such as anime. One of the anime is Hoozuki no Reitetsu which displays fantasy as the main background for the characters doing their stuff. The research method used is descriptive qualitative research method. The data analysis technique in this study is collecting data from the anime Hoozuki no Reitetsu, doing a sign analysis of the screenshoot using the "meaning triangle" Charles Sanders Peirce. Finally, look for the relationship between the results of the analysis of the signs in the anime and disaster groups in Japanese society. The results of the analysis show that the facts in the anime are described as Japanese companies issued various needs to punish sinful humans, because there are many factors such as changing the times, science and culture in Japan.